Optimization of Compressive Strength of Geopolymer Concrete Based on Rice Husk Ash and Fly Ash with Banana Stem Fiber for Rigid Pavement - Aura Syawwal Fasa; Yudi Setio Prabowo (International Journal of Science and Society, 2026)
Geopolymer concrete is an environmentally friendly alternative to Portland cement concrete by utilizing industrial and agricultural waste. This study aimed to investigate the effect of banana sheath fiber on the compressive strength of geopolymer concrete containing 95% fly ash and 5% rice husk ash (RHA), activated with 12 M sodium hydroxide (NaOH) and a sodium silicate to sodium hydroxide (Na₂SiO₃/NaOH) ratio of 2.0. An experimental laboratory method was conducted using 15 × 15 × 15 cm cube specimens with banana sheath fiber contents of 0%, 0.1%, and 0.2%. Compressive strength tests were performed at curing ages of 7, 14, and 28 days using a Compression Testing Machine (CTM) in accordance with SNI 1974:2011. The control mixture without fiber achieved the highest compressive strength of 33.9 MPa at 28 days and was the only mixture that met the target strength of 30 MPa. Mixtures containing 0.1% and 0.2% fiber achieved maximum strengths of 25.5 MPa and 28.5 MPa, respectively. Although fiber addition did not improve compressive strength, it reduced surface cracking after testing, indicating its potential to enhance the performance of geopolymer concrete for rigid pavement applications.